POLA ASUH ORANG TUA DAN KONFORMITAS TEMAN SEBAYA SERTA PENGARUHNYA TERHADAP KENAKALAN REMAJA - Rizawati Rizawati (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
Juvenile Delinquency is a form of conflicts that are not resolved properly due to improper parenting and the consequences of relationships with peers. Adolescents are vulnerable people, so the environment plays an important role in the formation of adolescent behavior both in the family environment and in the community, especially social relations with peers. This study aims to determine the effect of parenting and peer conformity on juvenile delinquency. The population of this study were all students of Muhammadiyah 1 Tangerang Selatan Vocational School totaling 440 students, while the research sample consisted of 200 students. Data collection using; 1. The Parental Authority Questionnaire Scale developed by Buri (1991), 2. The scale developed by the researcher based on the dimensions of Sears (2002) theory, 3. The scale that is also developed by researchers based on Jensen's (1985) theory dimensions. The data obtained were analyzed using multiple regression with SPSS version 17 software and for testing the construct validity using CFA (Confirmatory factor analysis) with the help of LISREL software version 8.7. The results showed that; 1. Parenting and peer conformity have a significant effect on juvenile delinquency, 2. The proportion of variance from juvenile delinquency that is influenced by independent variables is 55.6% and the remaining 44.4% is influenced by other variables outside this study.